Copper Effect of Feed Supplementation on Growth Performance in Fattening Pigs - Tiberiu Polen; Octavian Sorin Voia (Scientific Papers Animal Science and Biotechnologies, 2023)
In this study we aimed to follow the effect of copper supplementation from different sources and levels on growth performance and feed conversion mode, at fattening pigs. The research was done on 45 animals at the age of 95 days that were divided in 3 variants: V1=6 mg Cu/kg feed (CuSO4+5 H2O); V2=31.25 mg Cu/kg feed (CuSO4+5 H2O); V3=31.25 mg Cu/kg feed (Cu-polyphosphate glass source). The duration of trial was 90 days. In the growth period the average daily gain was significantly upper (p≤0.05) to V2 (773 g/day) and V3 (811 g/day) comparative with V1 (721 g/day). Feed conversion ratio was significantly lower to V2 (3.95 kg) and V3 (3.77 kg) than V1 (4.12 kg). Copper supplementation at 31.25 mg Cu/kg feed (V3) resulted in an increase in average daily gain up to 13.9% and feed conversion ratio was reduced to 9.3%, compared to the control group (V1).